TEKNIK DAN PEMASARAN KRIPIK SINGKONG UNTUK MENGATASI EKONOMI MASYARAKAT AKIBAT DAMPAK COVID 19 DESA SUMBERSEKAR KECAMATAN DAU KABUPATEN MALANG - Zainol Arifin; Cakti Indra Gunawan; Latif Fianto (JURNAL DAYA-MAS, 2023)
Management training for the Home Industry of cassava chips "Burung Pipit" includes planning, organizing, understanding and defining work (job description) to improve division performance. Financial Management in terms of bookkeeping of financial transactions aims to find out how much withdrawals and expenses are each season. By making a simple journal for each financial transaction, you can form and carry out a cash flow analysis. Training on cassava chip product training "Burung Pipit" aims to increase the selling value of processed products so that it is necessary to develop various processing training related to processing components such as handling cooking oil, cassava as a raw material, as well as management of other materials and equipment such as E-Marketing and technology appropriate as a technology medium for cassava chips home product industry. In the future, UD “Burung Pipit” cassava chips is expected to be able to promote and sell their products without being limited by time and place, so that it will accelerate business development efforts and improve the welfare of the Sumbersekar Dau Malang cassava chip Home Industry. Promotional media using the internet is currently very relevant where people are used to looking for something personal, company or agency needs using internet facilities. Surveys prove that 50% of home-based businesses or small and medium businesses are already using appropriate technology and the internet as their marketing instrument.